TRADITIONAL MACEDONIAN SAUSAGES WITH STARTER CULTURES - Silovska Nikolova, Aleksandra; Pejkovski, Zlatko; Belichovska, Daniela; Belichovska, Katerina (Institute of Knowledge Management, 2019)
The Krushevo sausage and The Vevchani Sausage - lukanec are authentic kinds of traditional sausages in The Republic of Macedonia. These traditional sausages are part of the domestic sausages group and, as such, they have very specific characteristics. They recently entered the world ark of flavours supported by the “Slow Food” organization. The purpose of this thesis is to examine whether the leek, in dry condition, as a natural source of nitrates, combined with the starter cultures Bactoferm CS-300 together with SafeProImporous, could produce satisfactory results for making the Krushevo sausage and The Vevchani sausage – lukanec. It has been concluded that, for both types of sausages, the desired color has been reached, without using nitrites which are harmful for our health. The dry leek can be used as a suitable substitute for the chard in powder. The starter cultures helped reaching better sensory characteristics (color of surface and cross section, flavor, scent, texture) of the product, thus getting a traditional product with standardized sensory characteristics and an extended expiry date without using any additives. By using starter cultures and dry leek when producing sausages, practically, the international E-symbols (additives) may be taken out from the label, thus satisfying the needs of the modern consumer. Nowadays, the modern consumers increase the awareness for healthy life, and so they change their diet habits. Having this in mind, they reduce consuming processed meat products or they consume natural processed meat products, which contain less amount of additives. The meat processing companies need to consider using starter cultures and alternative sources of nitrites, thus getting processed meat products with standardized sensory characteristics as well as extended expiry date without using harmful additives.